Efficacy of baricitinib in patients with moderate-to-severe rheumatoid arthritis with 3 years of treatment: results from a long-term study - Smolen, JS; Xie, L; Jia, B; Taylor, PC; Burmester, G; Tanaka, Y; Elias, A; Cardoso, A; Ortmann, R; Walls, C; Dougados, M (BMJ Publishing Group, 2020)
Background: Baricitinib (Bari) is an oral, selective and reversible Janus kinase 1 and 2 inhibitor approved for the treatment of adults with active RA. In addition to long-term safety which has been disclosed previously with data up to 7 years [1], an important clinical consideration is whether treatment efficacy can be maintained over the long term.